Identification Of Source Of Resistance Against Major Hemibiotrophic Foliar Fungal Pathogens Of Soybean (Journal of Plant Disease Sciences, 2018)
Field and glasshouse screening against soybean anthracnose (Colletotrichum truncatum), Alternaria leaf spot (Alternaria alternata) and Cercospora leaf spot (Cercopsora sojina) was taken during kharif 2016 at the Main Agricultural Research Station, Dharwad. Fifty eight genotypes were screened under natural epiphytotic condition, among them genotypes viz.,EC 107407 EC 107416 EC 14458 EC 14476 EC 242086 EC 291398 showed highly resistant reaction for Cercospora leaf spot and Alternaria leaf spot and moderately resistant reaction for anthracnose. Under artificial condition, among the ten genotypes screened by artificial inoculation, three genotypes viz., DSb 32, DSb 33 and DSb 34 were found highly resistant to all three diseases. The genotypes DSb 28-3 showed highly resistant reaction both in glasshouse and field conditions against Cercospora leaf spot, Alternaria leaf spot. The genotype JS 335 showed highly susceptible reaction to all the three diseases in both glasshouse and field conditions.
Keywords: Soybean; screening; genotype; resistance; foliar disease